1994
DOI: 10.1037/h0090219
|View full text |Cite
|
Sign up to set email alerts
|

Session effects, comparability, and managed care in the psychotherapies.

Abstract: Dose-effect and duration comparability studies provide direction for effective time guidelines for outpatient psychotherapy. Current managed care approaches appear inappropriate in emphasizing usage rather than effectiveness curves. Guidelines are suggested for basic, intermediate, and extended treatment with different goals, dosages, and managed care policies.Probably the most controversial feature of managed mental health care is limiting the duration of outpatient psychotherapy (Herron, 1992;Lowman, 1992). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Further examination of the relationship between the number of sessions attended and the outcome for clients in these centers is warranted because some contend that current managed-care accountability procedures are inappropriate. These critics claim that such procedures emphasize usage rather than session-by-session effectiveness and that building effectiveness curves may be more appropriate (Herron, Eisenstadt, Javier, & Primavera, 1994).…”
mentioning
confidence: 97%
“…Further examination of the relationship between the number of sessions attended and the outcome for clients in these centers is warranted because some contend that current managed-care accountability procedures are inappropriate. These critics claim that such procedures emphasize usage rather than session-by-session effectiveness and that building effectiveness curves may be more appropriate (Herron, Eisenstadt, Javier, & Primavera, 1994).…”
mentioning
confidence: 97%
“…It is unclear, however, at which point the number of therapy sessions begins to have no effect on client progress. Herron et al (1994) found that 10% to 18% of the patients demonstrated improvement by simply initiating therapy, 48% to 58% improved by eight sessions, 75% improved by 26 sessions and 85% improved by 52 sessions.…”
Section: Limitations Of Current Managed Care Organization Strategies mentioning
confidence: 98%
“…Herron et al (1994) report that long-term therapy is not necessarily better than short-term therapy. It is unclear, however, at which point the number of therapy sessions begins to have no effect on client progress.…”
Section: Certification Of Outpatient Psychotherapy Based On Treatmentmentioning
confidence: 99%